IMPLEMENTASI METODE LANGSUNG DALAM PEMBELAJARAN BAHASA ARAB (Studi Eksperimen Pada Mahasiswa Semester III Pendidikan Bahasa Arab) - Sudir Koadhi (Universitas Muhammadiyah Makassar, 2017)
This study aims to see the effect of direct method implementation in learning Arabic language on the third semester students of Arabic Language Education Faculty of Muhammadiyah University of Makassar, whether it could improve the mastery of skills in maharah kalam ?, both for students who belong to the average level and low level group. The method used in this research was an experimental method that‟s begun with pretest (preliminary test) to know the level of mastery of students' language skills, as well as to perform placement test. After doing treatment by applying direct method in learning Arabic skills, with the assumption that the method would be able to improve students' Arabic language skills were average and weak. So it was required posttest (final test) to find out how far the influence of the application of the method. From the results of the research, on the implementation of Direct Methods in Arabic learning, it could be concluded that (1) Direct Method implementation had enough influence in improving the speaking skill (maharatul kalam) in Arabic at the third semester student of Arabic Language Education (PBA) Faculty of Islamic Studies Unismuh Makassar. 2) third semester students of Arabic Language Education (PBA) Faculty of Islamic Studies Unismuh Makassar, well motivated to learn and improve speaking skill in Arabic through the implementation of Direct Method (Mubasyarah / Direct Method). Keywords: Direct method, speaking skill (maharatul kalam)